Deriving CME Density From Remote Sensing Data and Comparison to In‐Situ Measurements. Issue 1 (20th January 2021) - Temmer, M.; Holzknecht, L.; Dumbović, M.; Vršnak, B.; Sachdeva, N.; Heinemann, S. G.; Dissauer, K.; Scolini, C.; Asvestari, E.; Veronig, A. M.; Hofmeister, S. J.
Abstract: We determine the three‐dimensional geometry and deprojected mass of 29 well‐observed coronal mass ejections (CMEs) and their interplanetary counterparts (ICMEs) using combined Solar Terrestrial Relations Observatory ‐ Solar and Heliospheric Observatory white‐light data. From the geometry parameters, we calculate the volume of the CME for the magnetic ejecta (flux‐rope type geometry) and sheath structure (shell‐like geometry resembling the (I)CME frontal rim). Working under the assumption that the CME mass is roughly equally distributed within a specific volume, we expand the CME self‐similarly and calculate the CME density for distances close to the Sun (15–30 Rs) and at 1 AU. Specific trends are derived comparing calculated and in‐situ measured proton densities at 1 AU, though large uncertainties are revealed due to the unknown mass and geometry evolution: (1) a moderate correlation for the magnetic structure having a mass that stays rather constant ( cc ≈ 0.56 − 0.59), and (2) a weak correlation for the sheath density ( cc ≈ 0.26) by assuming the sheath region is an extra mass—as expected for a mass pile‐up process—that is in its amount comparable to the initial CME deprojected mass. High correlations are derived between in‐situ measured sheath density and the solar wind density ( cc ≈ −0.73) and solar wind speed ( cc ≈ 0.56) as measured 24 h ahead of the arrival of the disturbance. This gives additional confirmation that the sheath‐plasma indeed stems from piled‐up solar wind material. While the CME interplanetary propagation speed is not related to the sheath density, the size of the CME may play some role in how much material could be piled up. Key Points: (Interplanetary) Coronal mass ejections CME density evolution Modeling and observations